Why No Signals? Cerebral Anatomy Predicts Success of Intraoperative Neuromonitoring During Correction of Scoliosis Secondary to Cerebral Palsy. Issue 8 (December 2017) - Mo, Andrew Z.; Asemota, Anthony O.; Venkatesan, Arun; Ritzl, Eva K.; Njoku, Dolores B.; Sponseller, Paul D.
Abstract : Background: Intraoperative neuromonitoring (IONM) is widely used to reduce postoperative neurological complications during scoliosis correction. IONM allows intraoperative detection of neurological insults to the spinal cord and enables surgeons to react in real time. IONM failure rates can reach 61% in patients with cerebral palsy (CP). Factors decreasing the quality of IONM signals or making IONM impossible in CP patients undergoing scoliosis correction have not been well described. Methods: We categorized IONM data from 206 children with CP who underwent surgical scoliosis correction at a single institution from 2002 through 2013 into 3 groups: (1) "no signals, " if neither somatosensory-evoked potentials (SSEP) nor transcranial motor-evoked potentials (TcMEP) could be obtained; (2) "no sensory, " if no interpretable SSEP were obtained regardless of interpretable TcMEP; and (3) "no motor, " if no interpretable TcMEP were obtained regardless of interpretable SSEP. We analyzed preexisting neuroimaging, available for 93 patients, and neurological status of the full cohort against these categories. Statistical analysis of univariate and multivariate associations was performed using logistic regression. Odds ratios (ORs) were calculated with significance set at P <0.05. Results: Multivariate analysis showed significant associations of periventricular leukomalacia (PVL), hydrocephalus, and encephalomalacia with lack of meaningful and interpretable signals. Focal PVL (Fig. 1) was associated with no motor (OR=39.95; P =0.04). Moderate hydrocephalus was associated with no signals (OR=32.35; P <0.01), no motor (OR=10.14; P =0.04), and no sensory (OR=8.44; P =0.03). Marked hydrocephalus (Fig. 2) was associated with no motor (OR=20.46; P <0.01) and no signals (OR=8.83; P =0.01). Finally, encephalomalacia (Fig. 3) was associated with no motor (OR=6.99; P =0.01) and no signals (OR=4.26; P =0.03). Conclusion: Neuroanatomic findings of PVL, hydrocephalus, and encephalomalacia are significant predictors of limited IONM signals, especially TcMEP. Level of Evidence: Level IV.